Modeling of the stress–strain behavior of an epoxy-based nanocomposite filled with silica nanoparticles. (5th January 2016) - Dmitriev, Andrey I.; Häusler, Ines; Österle, Werner; Wetzel, Bernd; Zhang, Ga
Abstract: The method of movable cellular automata (MCA) was applied to simulate the stress–strain behavior of a nanocomposite consisting of an epoxy matrix and 6 vol.% silica nanoparticles. The size of the elements used for modeling was fixed at 10 nm, corresponding approximately to the diameter of the filler particles. Since not only the stress–strain response of the two constituents but also debonding of neighboring particles and granular flow was taken into account, plastic deformation as well as crack initiation and propagation could be simulated with the model. Modeling results were compared with tensile test results of both, pure epoxy as well as the epoxy–6 vol.% SiO2 composite. Since assuming bulk properties of the two constituents did not yield satisfactory results, slight modifications of the nanoparticle response functions and nanostructures were tested numerically. Finally, it was observed that only the assumption of slightly increased strength properties of the epoxy yielded good correlation between experimental and modeling results. This was attributed to an increased cross linking of the epoxy caused by the presence of silica nanoparticles. Graphical abstract: Highlights: We prepared epoxy-based composites filled with silica nanoparticles. Mechanical properties were measured and compared to neat epoxy. A Movable Cellular Automata method was applied for simulating tensile tests. Slight modifications of the response functions provided good fits with experiments. Modification of epoxy properties by addition of silica nanoparticles was suggested.